Gluteus Muscle Activation Training On Myogenic Low Back Pain: A Case Report - Bagas Anjasmara; Soffil Yudha Mulyandi; Suci Ariani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Myogenic low back pain is one of the musculoskeletal disorders caused by dysfunction of muscles and supporting soft tissues such as tendons and ligaments. This condition is often associated with repetitive activities, excessive muscle use, and poor postural habits during daily activities. Myogenic low back pain can lead to reduced functional capacity and decreased productivity, therefore requiring appropriate and comprehensive management. This study aimed to evaluate the effect of a combination of physiotherapy interventions, particularly gluteus medius muscle activation exercises, in reducing pain and improving functional ability in a case of myogenic low back pain. This study used a case report design conducted in a private physiotherapy clinic. The subject of this study was a 22-year-old male diagnosed with myogenic low back pain who complained of pain during physical activities. The physiotherapy intervention program consisted of transcutaneous electrical nerve stimulation (TENS), manual therapy in the form of muscle release techniques, and gluteus medius activation exercises. The intervention was administered twice a week for four weeks, totaling eight therapy sessions. The outcomes of the intervention were evaluated using the Visual Analog Scale and the Oswestry Disability Index. The results showed a reduction in pain intensity and an improvement in the patient’s functional activity after eight therapy sessions. These findings indicate that a physiotherapy approach combining electrotherapy modalities, manual therapy techniques, and muscle activation exercises can contribute positively to improving the clinical condition of patients with myogenic low back pain.